The Effect Of Service Quality, Product Quality, And Chatime Product Promotion On Customer Satisfaction (Case Study Of Chatime Customers In The Central Jakarta Region) - Eka Erlinda, Ulfania; Purnama, Suryari; Tamzil, Fachmi (Pandawan, 2022)
This study aims to determine the effect of service quality, product quality, and promotion of Chatime products on customer satisfaction (a case study of Chatime customers in the Central Jakarta Region). The population in this study are all Chatime customers who make direct purchases at outlets. The sample in this study was taken by non-probability sampling method using purposive sampling technique as many as 185 respondents. The data collection method used in this study was through an online questionnaire—data processing using Multiple Regression Analysis. The results of this study indicate: (1) service quality has a positive and significant effect on customer satisfaction; (2) product quality has a positive and significant effect on customer satisfaction; (3) promotion has a positive and significant effect on customer satisfaction; (4) service quality, product quality, and promotion have a simultaneous positive, and significant effect on Chatime customer satisfaction in the Central Jakarta area; (5) the variable that has a dominant influence on Chatime customer satisfaction in the Central Jakarta area is the promotion variable.